Intuition in judgment and decision making - Plessner, Henning; Betsch, Cornelia; Betsch, Tilmann (Lawrence Erlbaum Associates, 2008)
The central goal of this volume is to bring the learning perspective into the discussion of intuition in judgment and decision making. The book gathers recent work on intuitive decision making that goes beyond the current dominant heuristic processing perspective. However, that does not mean that the book will strictly oppose this perspective. The unique perspective of this book will help to tie together these different conceptualizations of intuition and develop an integrative approach to the psychological understanding of intuition in judgment and decision making. Accordingly, some of the ch
Includes bibliographical references and index
Keywords: Konferenzschrift; Entscheidungsfindung; Intuition